Proceedings of the 2019 CHI Conference on Human Factors in Computing Systems 2019
DOI: 10.1145/3290605.3300420
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Perception of Smartphone Notifications Using Skin Conductance Responses

Abstract: Today's smartphone notification systems are incapable of determining whether a notification has been successfully perceived without explicit interaction from the user. If the system incorrectly assumes that a notification has not been perceived, it may repeat it redundantly, disrupting the user and others (e.g., phone ringing). Or, if it incorrectly assumes that a notification was perceived, and therefore fails to repeat it, the notification will be missed altogether (e.g., text message). Results from a labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…However, since these rewards may not be immediate in the context of IM, they may create a state of increased emotional arousal, especially when the rewards (i.e., the response) eventually arrive in the form of notifications on the smartphone. Prior research has already shown that arousal induced by smartphone notifications is different from arousal due to arbitrary stimuli in the environment ( Fortin et al, 2019 ). As individuals are notified about incoming messages, “the dopaminergic reward circuit [gets activated], leading the user to anticipate and seek these [social] rewarding notifications” ( Veissière and Stendel, 2018 , p. 4).…”
Section: Discussionmentioning
confidence: 99%
“…However, since these rewards may not be immediate in the context of IM, they may create a state of increased emotional arousal, especially when the rewards (i.e., the response) eventually arrive in the form of notifications on the smartphone. Prior research has already shown that arousal induced by smartphone notifications is different from arousal due to arbitrary stimuli in the environment ( Fortin et al, 2019 ). As individuals are notified about incoming messages, “the dopaminergic reward circuit [gets activated], leading the user to anticipate and seek these [social] rewarding notifications” ( Veissière and Stendel, 2018 , p. 4).…”
Section: Discussionmentioning
confidence: 99%
“…Name • Logistic Regression: As a popular statistical tool in HCI and CSCW quantitative analysis [21,38,56,69], Logistic Regression in its basic form uses a logistic (sigmoid function) function to model a binary dependent variable [69]. In our work, the dependent variable is the dropout's outcome [69].…”
Section: Models With Hmm Engagement Features (Ef) Models Without Hmm ...mentioning
confidence: 99%
“…Although several studies have examined the negative impact of smartphone addiction [47][48][49][50][51][52][53][54], little is known regarding its behavioral and physiological basis, especially in the context of mother-infant interactions. A major way in which we can assess reactivity to smartphone distraction during mother-infant interaction is by measuring changes in physiological function of mothers' peripheral nervous system as well as her gaze patterns during interactions with her infant that also involve the smartphone.…”
Section: Introductionmentioning
confidence: 99%